Community education - Piasecki, Nicole Susan, author; Candelaria Fletcher, Harrison, advisor; Vara, Vauhini, committee member; Hausermann, Heidi, committee member (Colorado State University. Libraries, 2024)
Community Education is a collection of creative nonfiction essays that wonders about the positive and negative space created by silence. When normative social structures silence honest conversation and speech, what damage is done? Can it be remediated? How might one learn to live freely, speak openly, and translate fear into a generative force. Many of the essays in Community Education chronicle the coming-of-age story of a queer female in rural and suburban Michigan in the late 1990s. The narrator struggles to connect with family and friends after losing her dad in a tragic mass shooting. The disconnect caused by her grief compounds when she leaves for college and begins questioning her sexuality. Without positive stories or queer role models, she believes she must keep secrets to avoid disappointing the people she loves or becoming a social outcast. She finds a sense of belonging—sometimes intentionally and other times by accident—in communities of strangers who help her untangle her lifetime of internalized narratives about womanhood and queerness. She meets strangers in early-America-Online chatrooms and joins a friend group of older feminist lesbians who call her "baby dyke" but treat her like an adult. She meets queer people and allies at gay bars and music festivals and as a member of a gay ice hockey team. She leaves her home state of Michigan shortly after graduating from college and starts fresh in the Colorado Rockies. Everywhere the narrator goes, strangers and acquaintances step in to draw the narrator out of isolation and offer lessons about living she never received in school or at home. This community education helps her feel more at home in her body and country. It gives her the courage to assert herself. Through finding her voice, she learns the truth has its own consequences and rewards. At the core, this book is about seeking home outside the geography of self, in order to eventually find home inside.